Systematic Literature Review: Peran Literasi Digital dalam Penguatan Kurikulum Pembelajaran Abad Ke-21 Di Sekolah Menengah - Haikal, Ahmad; Pertiwi, Azarine Eka Bina; Afrinadya, Ifa; Marthaliakirana, Angsoka Dwipayana; Usman, Usman (Paedagogie, 2026)
This study aims to examine the role of digital literacy in strengthening the 21st-century learning curriculum at the secondary school level through a Systematic Literature Review (SLR) approach. The review analyzed 25 scholarly articles published between 2022 and 2025, which were systematically retrieved from Google Scholar, DOAJ, Garuda, and SINTA databases. The literature selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, including identification, screening, eligibility assessment, and inclusion stages. Data were analyzed using a descriptive thematic approach, resulting in four main themes: teachers’ digital literacy and pedagogical competence, students’ digital literacy and 21st-century skills, integration of digital literacy into the curriculum, and challenges as well as institutional support for digital literacy implementation. The findings indicate that digital literacy plays a strategic role in strengthening the 21st-century curriculum by enhancing teachers’ pedagogical competence, fostering students’ critical thinking, collaboration, and self-directed learning skills, and supporting the development of adaptive and contextual curriculum designs. The review also highlights that successful digital literacy implementation is strongly influenced by institutional readiness, including policy support, educational leadership, equitable digital infrastructure, and sustained pedagogically oriented teacher training. Therefore, digital literacy should be positioned as a structural foundation for strengthening the 21st-century learning curriculum in secondary schools to promote an adaptive, inclusive, and sustainable education system in the context of global digital transformation.